Self-nanoemulsifying drug delivery system (SNEDDS) of piroxicam: evaluation on anti-inflammantory activity in wistar rats - Yudha Rizky Nuari; Iis Wahyuningsih; Sekar Prabawati (Pharmaciana, 2021)
Piroxicam is a non-steroidal anti-inflammatory drug (NSAID) that is commonly used for arthritis, gout, and other musculoskeletal disorders. Piroxicam is poorly soluble in water and according to the biopharmaceutical drug classification system (BCS) is classified as a Class II drug with good permeability but poor dissolution. The self-nanoemulsifying drug delivery system (SNEDDS) has been extensively employed to improve the dissolution and absorption of water-insoluble drugs within the gastrointestinal tract, leading to enhanced oral bioavailability and increased therapeutic effect of the loaded drugs. Therefore, the present study aims to evaluate the anti-inflammatory activity of piroxicam-loaded SNEDDS as compared to conventional piroxicam suspension that was observed in male Wistar strain rats. The SNEDDS was tailored from a mixture of oleic acid, tween 80, and propylene glycol. Twenty male Wistar strain rats (aged 2-3 months, weighed 150-250g) were selected and were divided equally into 4 different groups receiving 1% PVP, SNEDDS carrier, piroxicam suspension (1.8 mg/Kg BW), and SNEDDS piroxicam (1.8 mg/Kg BW). Acute inflammation was induced by a carrageenan-induced paw edema model where the carrageenan was injected sub plantar in the hind paw of the rats to induce edema. Several parameters including paw edema volume, AUC0-6, and percent anti-inflammatory effect, were measured to evaluate the anti-inflammatory activity experienced in each group. At the end of this study, the piroxicam SNEDDS group significantly demonstrated better protection from paw edema compared to the piroxicam suspension group (Ï<0.05), suggesting that SNEDDS may enhance the anti-inflammatory activity of piroxicam.